Airborne observations of Arctic air mass transformations during the HALO-(AC)3 campaign - Klingebiel, M.; Schäfer, M.; Kirbus, B.; Maherndl, N.; Becker, S.; Brückner, M.; Jäkel, E.; Lonardi, M.; Luebke, A.E.; Maahn, M.; Müller, H.; Röttenbacher, J.; et al. (Universität Leipzig, 2022)
The HALO-(AC)3 campaign was conducted in March and April 2022 to investigate warm air intrusions into the Arctic and marine cold air outbreaks. In coordinated flights over the Arctic, the High Altitude and Long Range Research Aircraft (HALO), equipped with a remote sensing payload and dropsondes, investigated these air mass transformations together with the research aircraft Polar 5 and Polar 6. In this report, we give an overview about the research flights and preliminary results from projects, which are carried out by employees of the Leipzig Institute for Meteorology (LIM). Die HALO-(AC)3 Kampagne wurde im März und April 2022 durchgeführt, umWarmlufteinbrüche in die Arktis und marine Kaltluftausbrüche zu untersuchen. Das 'High Altitude and Long Range Research Aircraft' (HALO), ausgestattet mit Instrumenten zur Fernerkundung und Standardmeteorologiesonden, untersuchte zusammen mit den Forschungsflugzeugen Polar 5 und Polar 6, in koordinierten Flügen über der Arktis, diese Veränderungen der Luftmassen. In diesem Bericht wird eine Übersicht über die durchgeführten Forschungsflüge gegeben und Forschungsprojekte werden vorgestellt, welche von Mitarbeitern des Leipziger Instituts für Meteorologie (LIM) durchgeführt werden.